Disruption of barley immunity to powdery mildew by an in-frame Lys-Leu deletion in the essential protein SGT1. Issue 2 (22nd December 2020) - Chapman, Antony V E; Hunt, Matthew; Surana, Priyanka; Velásquez-Zapata, Valeria; Xu, Weihui; Fuerst, Greg; Wise, Roger P
Abstract: Barley ( Hordeum vulgare L.) Mla (Mildew resistance locus a ) and its nucleotide-binding, leucine-rich-repeat receptor (NLR) orthologs protect many cereal crops from diseases caused by fungal pathogens. However, large segments of the Mla pathway and its mechanisms remain unknown. To further characterize the molecular interactions required for NLR-based immunity, we used fast-neutron mutagenesis to screen for plants compromised in MLA-mediated response to the powdery mildew fungus, Blumeria graminis f. sp. hordei . One variant, m11526, contained a novel mutation, designated rar3 ( required for Mla6 resistance3 ), that abolishes race-specific resistance conditioned by the Mla6, Mla7, and Mla12 alleles, but does not compromise immunity mediated by Mla1, Mla9, Mla10, and Mla13 . This is analogous to, but unique from, the differential requirement of Mla alleles for the co-chaperone Rar1 (required for Mla12 resistance1). We used bulked-segregant-exome capture and fine mapping to delineate the causal mutation to an in-frame Lys-Leu deletion within the SGS domain of SGT1 (Suppressor of G-two allele of Skp1, Sgt1ΔKL308–309 ), the structural region that interacts with MLA proteins. In nature, mutations to Sgt1 usually cause lethal phenotypes, but here we pinpoint a unique modification that delineates its requirement for some disease resistances, while unaffecting others as well as normal cell processes. Moreover, the data indicate that the requirement of SGT1 for resistance signaling by NLRs can be delimited to single sites on the protein. Further study could distinguish the regions by which pathogen effectors and host proteins interact with SGT1, facilitating precise editing of effector incompatible variants.